2009
DOI: 10.1002/sia.3136
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion behaviour of mechanically polished AA7075‐T6 aluminium alloy

Abstract: In the present study, the effects of mechanical polishing on the microstructure and corrosion behaviour of AA7075 aluminium alloy are investigated. It was found that a nano-grained, near-surface deformed layer, up to 400 nm thickness, is developed due to significant surface shear stress during mechanically polishing. Within the near-surface deformed layer, the alloying elements have been redistributed and the microstructure of the alloy is modified; in particular, the normal MgZn 2 particles for T6 are absent.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 8 publications
2
34
0
Order By: Relevance
“…[4,6,[8][9][10][11][12][13][14][15][16][17][18] The near-surface deformed layers are characterized by an ultrafine-grained microstructure, consisting of a large population of grain boundaries which represents high stored energy. At elevated temperatures, the ultrafine grains in the near-surface deformed layer are susceptible to grain growth.…”
Section: Introductionmentioning
confidence: 99%
“…[4,6,[8][9][10][11][12][13][14][15][16][17][18] The near-surface deformed layers are characterized by an ultrafine-grained microstructure, consisting of a large population of grain boundaries which represents high stored energy. At elevated temperatures, the ultrafine grains in the near-surface deformed layer are susceptible to grain growth.…”
Section: Introductionmentioning
confidence: 99%
“…The near-surface deformed layer has a significant influence on the electrochemical and corrosion behavior, the joining and welding behavior, optical properties, and potentially mechanical properties of the alloys such as formability and bendability. [5,[9][10][11][12][13][14][15][16][17][18][19] Understanding the evolution of the near-surface deformed layer through conventional fabrication processing is, therefore, both of technological importance and of significant scientific interest.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Although conventional fabrication and finishing processes, for example rolling, do not strain the bulk material to the same extent as ECAE, it has been shown that the surface and near-surface regions of alloy sheet are subjected to enhanced shear deformation. As a consequence, a heavily deformed near-surface layer, up to a few microns in thickness, comprising ultrafine grains with oxide-decorated boundaries and fine dispersoids, [5][6][7][8][9][10][11][12][13] is developed. The near-surface deformed layer has a significant influence on the electrochemical and corrosion behavior, the joining and welding behavior, optical properties, and potentially mechanical properties of the alloys such as formability and bendability.…”
Section: Introductionmentioning
confidence: 99%
“…Liu [12] reported that that overaging and dissolving of the metastable precipitates lead to the decrease in the hardness in the WZ. But the presence of the fine equiaxed grains and the resolution of the dissolved precipitates partially remedy the loss of hardness.…”
Section: Hardness Testingmentioning
confidence: 99%